Acetate Does Not Affect Palmitate Oxidation and AMPK Phosphorylation in Human Primary Skeletal Muscle Cells - González Hernández, Manuel A.; Blaak, Ellen E.; Hoebers, Nicole T. H.; Essers, Yvonne P. G.; Canfora, Emanuel E.; Jocken, Johan W. E. (Frontiers in Endocrinology, 2021)
Our recent in vivo human studies showed that colonic administration of sodium acetate (SA) resulted in increased circulating acetate levels, which was accompanied by increments in whole-body fat oxidation in overweight-obese men. Since skeletal muscle has a major role in whole-body fat oxidation, we aimed to investigate effects of SA on fat oxidation and underlying mechanisms in human primary skeletal muscle cells (HSkMC). We investigated the dose (0–5 mmol/L) and time (1, 4, 20, and 24 h) effect of SA on complete and incomplete endogenous and exogenous oxidation of 14C-labeled palmitate in HSkMC derived from a lean insulin sensitive male donor. Both physiological (0.1 and 0.25 mmol/L) and supraphysiological (0.5, 1 and 5 mmol/L) concentrations of SA neither increased endogenous nor exogenous fat oxidation over time in HSkMC. In addition, no effect of SA was observed on Thr172-AMPKα phosphorylation. In conclusion, our previously observed in vivo effects of SA on whole-body fat oxidation in men may not be explained via direct effects on HSkMC fat oxidation. Nevertheless, SA-mediated effects on whole-body fat oxidation may be triggered by other mechanisms including gut-derived hormones or may occur in other metabolically active tissues.